2012
DOI: 10.1080/17445647.2012.668425
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphological map of the NW Coast of the Island of Malta (Mediterranean Sea)

Abstract: This paper presents the results of geomorphological investigations carried along the north-western coast of the Island of Malta. Field surveys, accompanied by aerial photo-interpretation, have led to the production of a geomorphological map at 1:7500 scale which outlines the main processes and related landforms. The latter are the result of the complex interplay of structural, gravitational, coastal and karst processes. Particular attention was devoted to the recognition, identification and mapping of landslid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 8 publications
0
57
0
1
Order By: Relevance
“…This difference in the coastal morphology is linked to the development of a northeastwards tilting in response to the fault system activity, also responsible for the forcing of the surface waters in a WSW-ENE direction and the formation of NE-oriented fluvial valleys (Alexander, 1988;Biolchi et al, 2016). Wide sectors of NW coast of Malta are characterised by the presence of extensive landslides, mainly rock spreads and block slides (Devoto et al, 2012(Devoto et al, , 2013Piacentini et al, 2015). These slow-moving landslides detach and move hundreds of limestone blocks from the karst plateaus towards the sea, forming peculiar coastal landforms named "rdum" by locals.…”
Section: The Study Areamentioning
confidence: 99%
“…This difference in the coastal morphology is linked to the development of a northeastwards tilting in response to the fault system activity, also responsible for the forcing of the surface waters in a WSW-ENE direction and the formation of NE-oriented fluvial valleys (Alexander, 1988;Biolchi et al, 2016). Wide sectors of NW coast of Malta are characterised by the presence of extensive landslides, mainly rock spreads and block slides (Devoto et al, 2012(Devoto et al, , 2013Piacentini et al, 2015). These slow-moving landslides detach and move hundreds of limestone blocks from the karst plateaus towards the sea, forming peculiar coastal landforms named "rdum" by locals.…”
Section: The Study Areamentioning
confidence: 99%
“…In the northern part of the archipelago, the WSW-ENE fault system is responsible for a horst-and-graben structure that extends from the Great Fault to SE Gozo (Illies 1981;Alexander 1988;Devoto et al 2012). Here, the landscape is characterized by ridges and plateaus made up of Upper Coralline Limestone alternating with valleys locally filled by alluvial sediments.…”
Section: Regional Settingmentioning
confidence: 99%
“…The tilting, the fault systems and the different mechanical properties of the rocks (limestones v. clays) control the geomorphology of the Maltese Islands (Alexander 1988;Magri 2006;Devoto et al 2012;Biolchi et al 2015). In the northern part of the archipelago, the WSW-ENE fault system is responsible for a horst-and-graben structure that extends from the Great Fault to SE Gozo (Illies 1981;Alexander 1988;Devoto et al 2012).…”
Section: Regional Settingmentioning
confidence: 99%
“…In the first research stages, emerged coastal landslides were identified, mapped [4] and monitored [3] along the north-west coast of the Island of Malta. Further on, the research moved underwater to investigate the continental shelf.…”
Section: Emerged and Submerged Landslide Featuresmentioning
confidence: 99%